PENATAAN SISTEM DATABASE PERPUSTAKAAN SMAN MENGANTI GRESIK DENGAN MS ACCESS - Fitriani, Fenny; Pramesti, Wara; Anandyani, Aliffia Rahma; Canta, Himawan Widia (Kanigara, 2022)
The COVID-19 pandemic does not only affect health but also affects the system of activities in the education aspect. In the implementation of learning, these activities are carried out online. The impact is the need for online learning resources that are easily accessible by students so that learning achievement can still be achieved. One source of learning that can be obtained is by accessing the library online. However, the reality in the field is that not all schools have library databases that are processed using database software so the integration process into online libraries is still difficult to do. SMAN Menganti Gresik is one of the schools experiencing these problems. Based on this, it is necessary to arrange the initial database system owned by the school. Initial database setup is done using Ms. Access. This database arrangement activity is intended as the initial process of creating an online school library. In addition, the arrangement of this database is intended to facilitate the administrative system of activities in the school library. The library database arrangement carried out at Menganti Gresik Senior High School was carried out by making special menus for school visitors, special menus for visitors from outside the school, and special menus for users.